Poetics of Curriculum, Poetics of Life An Exploration of Poetry in the Context of Selves, Schools, and Society - Vaquer, Mary-Elizabeth.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2016)
Through multiple lenses of curriculum studies, the author explores how poetry is situated in the pedagogical world. Her work aims to illuminate how poetry is studied in schools and how these practices of studying poetry give poetry its cultural identity. Each chapter is guided by insight from John Dewey s Art as Experience which promotes explorations of opportunities for students to have profound experiences with poetry and art in schools. The purpose of this book is not to offer a prescription for teachers to use in their classrooms. This is not an outline regarding how someone should include poetry in a lesson plan. Rather, the author explores why poetry is important in our lives and how poetry can contribute to opening avenues for new possibilities through imagination and transformation based on phenomenological experience and scholarship. She explores poetry through Dewey s notion of aesthetics across diverse aspects of meaning making through poetry in a contemporary context. She also explores the influences that poetry has on the curriculum of our lives, and the influence that our lived curriculum has on the future of poetry. .
Acknowledgements -- Prelude -- A Sonnet: When Night Hangs Low -- A Sestina: O Muses, May You Come -- Free Verse with Pre-Commentary: The I/Eye of Beginning: The Importance of a Renewed Focus on Writing -- Interlude -- Poetry and Curriculum Align -- Curriculum and Poetry Meet -- Nature -- Knowledge and Culture Creation -- Autobiography -- The Regressive -- Progressive -- Therap-oetr-y -- Analytical -- Synthetical -- Preconscious Realms of Experience -- Expanded Sources of Literature -- Infinite Possibilities -- Personal Liberty and Emancipation -- The Means and the Ends -- Political and Social Implications -- New Language, New Freedom -- Interlude -- Poetry in a Standardized and Commodified World -- In Their Own Words -- Stolen Experience -- Hybridization and Mathematization -- Art and the Individual -- The Individual -- Kozol, Inequity, and Individualism -- Imitation -- Freeplay and Deconstruction -- Taking It Back -- Interlude -- Revisiting the Outdated: Form, Rhythm, and Performance in Poetry -- Psychology of Form -- Milktongue, Goatfoot, and Twinbird -- Form and Class -- Form and Possibility -- Poetry in Practice -- The Aural/Oral Element -- Memorization -- Reading out Loud -- Ultimately -- Interlude -- Minimalism, Creative Writing, and the Reader/Writer Connection -- Statement and Expression -- Minimalism? -- Reception Theory -- Genre -- The Human Text -- Différance and the Dearth of Essence -- Who Owns Writing? -- The Necessary Deconstruction -- The Efferent and the Aesthetic -- Le Grand Metanarrative -- Minimalism as Translation -- Analogies of Photography/Minimalism -- A Musical Consideration -- And Beyond -- Interlude -- Art as Experience through Dwelling, Lingering, and Loafing -- Transcendence -- Catharsis -- Being Connected -- So-Called Best Practices -- Solitude -- Dwelling -- Lingering -- Loafing -- The Art of Idleness -- Interlude -- Friends in Low Places: Poetry up, Down, and All Around -- The High and the Low of It -- But First, the Obvious: Poetry and Rap Music -- Slang and Stuff -- Speaking of New Languages -- Even Stranger? -- Poetry, Naturally -- Dimming the Lights -- Addendum -- References. .
Keywords: Education; Education; Education, general; Electronic books